Analisis Kompetensi Pedagogik Guru dalam Melaksanakan Pembelajaran Berbasis Blended Learning di Sekolah Dasar - Purwono Purwono; Novi Sagita Arianti; Ramdhan Witarsa Witarsa; Molli Wahyuni4 (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
This study aims to describe the pedagogic competence of teachers in implementing blended learning-based learning in elementary schools. The research method used is descriptive qualitative research method, with preparatory steps, field work, and data analysis. The data sources were all 24 teachers of SDN 001 Salo, consisting of 3 male teachers and 21 female teachers. The data collection technique used is teacher pedagogic competency analysis and observation. The research instrument used was the teacher's pedagogic analysis sheet and the observation sheet for the implementation of blended learning-based learning. The data analysis technique was carried out using qualitative data analysis techniques. The results showed that the teacher's pedagogic competence seen from the teaching experience was at a good level. The teacher's pedagogic competence in implementing blended learning-based learning is at a good level. The conclusion of this study is that the teacher's pedagogic competence in implementing blended learning-based learning is at a good level. Elementary school teachers need continuous training and mentoring in order to maintain and improve their pedagogical competence.